Between Islamic and Western Education: The Educational Dichotomy in ‘Abd al-Raḥmān al-Naḥlāwī’s Thought - Ahmad Natsir; Didin Wahyudin; Hafidh Aziz; Hasbulloh Nadaraning (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This research aims to invigorate the discourse on the educational thought of Al-Nahlawi, a figure frequently referenced yet seldom critically examined in Indonesia. Specifically, this study aims to: (1) Analyze the major ideas and ideological underpinnings of Al-Nahlawi's thoughts; (2) Trace the influence of the socio-political context of Syria on his work; and (3) Reveal the dichotomization of Western vs. Islamic education in his discourse. To achieve these objectives, this study employs the method of hermeneutic analysis to examine his major ideas and critical discourse analysis based on Fowler's model to investigate the diction and underlying ideology of his language. The research concludes that: Al-Naḥlāwī's thinking was significantly influenced by Syria's political dynamics and his concerns about the Islamic revival, which led him to adopt a stance of resistance against the West. His central idea focuses on returning humanity to its innate nature (fitrah) through the application of ideal Islamic educational principles, covering objectives, subject matter, curriculum, and methods. The primary conclusion of this study is that Al-Naḥlāwī's critique of Western education—which he describes with vocabulary such as